2000
DOI: 10.2337/diabetes.49.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin-induced diabetes and insulin treatment on the hypothalamic melanocortin system and muscle uncoupling protein 3 expression in rats.

Abstract: Hypothalamic melanocortins are among several neuropeptides strongly implicated in the control of food intake. Agonists for melanocortin 4 (MC-4) receptors such as -melanocyte-stimulating hormone ( -MSH), a product of proopiomelanocortin (POMC), reduce food intake, whereas hypothalamic agouti-related protein (AgRP) is a MC-4 receptor antagonist that increases food intake. To investigate whether reduced melanocortin signaling contributes to hyperphagia induced by uncontrolled diabetes, male Sprague-Dawley rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
88
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 55 publications
15
88
1
1
Order By: Relevance
“…However, increases of AgRP mRNA in response to both fasting and genetic leptin deficiency are substantially greater than observed for NPY mRNA levels, whereas such differences are not apparent in STZ-diabetic rats. 72 Thus, although NPY and AgRP are both upregulated in the arcuate nucleus in response to the same stimuli, the magnitude of this response may differ. Distinct mechanisms may therefore govern the control of NPY and AgRP biosynthesis.…”
Section: Agouti-related Peptide and The Melanocortin Systemmentioning
confidence: 99%
“…However, increases of AgRP mRNA in response to both fasting and genetic leptin deficiency are substantially greater than observed for NPY mRNA levels, whereas such differences are not apparent in STZ-diabetic rats. 72 Thus, although NPY and AgRP are both upregulated in the arcuate nucleus in response to the same stimuli, the magnitude of this response may differ. Distinct mechanisms may therefore govern the control of NPY and AgRP biosynthesis.…”
Section: Agouti-related Peptide and The Melanocortin Systemmentioning
confidence: 99%
“…Recent investigations (13,21) have demonstrated that UCPs can prevent mitochondrial ROS formation. The different members of the UCP family have distinct tissue distributions (19,22,23). Tissue localization as well as regulation confer different roles for the family members.…”
mentioning
confidence: 99%
“…For example, UCP1 is strictly restricted to brown adipose tissue, and its principal function is believed to be the generation of body heat (19,24). UCP3 tissue distribution is predominantly limited to skeletal muscle, whereas UCP2 expression is widespread in spleen, lung, stomach, white adipose tissue, and brain (23,25). Both UCPs regulate energy metabolism and weight regulation (19,20,26).…”
mentioning
confidence: 99%
“…Sub-populations of POMC neurons have been shown to co-express GABA and glutamate (Table 2). Perhaps not surprisingly, POMC/ CART neurons are regulated by insulin, leptin and ghrelin (Havel et al 2000, Cowley et al 2001, Balthasar et al 2004. Peripheral ghrelin peptide indirectly inhibits the activity of POMC/CART neurons in mice (Cowley et al 2003), but POMC/CART neurons may also be directly modulated by ghrelin-expressing neurons via synaptic communication (Guan et al 2008).…”
Section: Pomc/cart-expressing Neuronsmentioning
confidence: 99%